Familial aggregation of major depressive disorder in an African‐American community. Issue 7 (21st May 2018) - Murphy, Eleanor; Gangwisch, James E.; Matsunaga, Janet T.; Ottman, Ruth
Abstract: Background: African Americans (AAs) with major depressive disorder (MDD) experience more impairment and poorer treatment outcomes relative to Whites, yet are underrepresented in family studies of MDD. This is the first study to investigate the familial aggregation of major depression among AAs. Methods: Participants' reports of depression from clinical and family history (FH) interviews were used to examine depression rates among 435 first‐degree relatives and half‐siblings of 63 depressed cases and 222 relatives of 33 nondepressed controls. Binary logistic regression was used to compute odds ratios (ORs) for FH of MDD and level of trauma exposure (high and low) in cases versus controls. Poisson regression models with generalized estimating equations were used to assess MDD in relatives of cases versus relatives of controls. Results: Cases and controls did not differ in either FH of MDD (OR = 1.2, 95% confidence interval [CI] = 0.5–2.9), or prevalence of MDD in relatives (relative risk [RR] = 1.5, 95% CI = 0.8–2.5). However, exposure to high trauma was associated with increased risk of MDD (OR = 3.0, 95% CI = 1.22–7.17) and the combined effect of FH and trauma was greater than expected under an additive model. Similarly, the RR for MDD among relatives of cases with high‐trauma levels was 2.2 (1.24–4.2), compared to relatives of controls with low trauma. Conclusion: The effect of FH of MDD appears to be exacerbated among individuals exposed to high trauma. Replication and further research on the chronology and subtypes of trauma and MDD, and their interactions, remain essential in AA populations.